AMBIGUITAS BAHASA PADA BERITA ONLINE DALAM SITUS TRIBUNNEWS.COM BULAN DESEMBER 2018 - Gustin, Ayu Salina; Sinaga, Mangatur; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is to describe grammatical ambiguity and lexical ambiguity on online news in the site of tribunnews.com in December 2018. This study uses a qualitative descriptive method. Data obtained using reading techniques and note taking techniques. Then, the data is analyzed by reading the news text first then recording the parts according to the problems to be studied using a small book. From the data obtained in the online news on the site of tribunnews.com in December 2018, the types of grammatical ambiguity found include grammatical ambiguity based on punctuation and conjunctions, then grammatical ambiguity caused by branched phrases. Then the type of lexical ambiguity found is lexical ambiguity based on the form of shifting use, based on the form of specialization in the social environment, based on the form of figurative language, based on a form of understanding of incomplete meanings, based on forms of foreign influence, based on homonymy forms.Key Words: Language Ambiguity, Online News, Tribunnews.Com